Optimizing shipping routes to minimize cost using particle swarm optimization - Rahman, Annur; Asih, Hayati Mukti (International Journal of Industrial Optimization, 2020)
Product shipping is important in the economic process in the company. Efficient product shipping routes should provide low transportation costs. This study based on a case company of CV. Kayana, a distributor of â€œSari Rotiâ€, has 4 motorbikes and 2 cars. Each vehicle has their own shipping routes. Nowadays, high distance for each route results on high transportation cost. Therefore, the objective of this study to minimize the distance and cost of product shipping by developing shipping algorithm using Particle Swarm Optimization (PSO) for Traveling Salesman Problem (TSP). The MATLAB software was employed to solve this problem. The solution is obtained by varying the amount of particles and number of iterations. Experimental results proved that the developed PSO is enough effective and efficient to solve shipping routes problem. The results show the proposed model have lower distance and transportation cost. It helps the company in determining the routes for product shipping with minimum transportation cost.